The Use of a Functional and Immunologic Assay for Plasma Protein C in the Study of the Heterogeneity of Congenital Protein C Deficiency - Bertina, R M; Broekmans, A W; Es, C Krommenhoek-van; Wijngaarden, A van (Thrombosis and Haemostasis, 1984)
Protein C is a vitamin K dependent protein involved in blood coagulation. A congenital deficiency in protein C antigen - which inherits as an autosomal dominant disorder - has been reported to be associated with a high risk for thrombo-embolic disease at relatively young age. In the present paper we report on the development of a functional assay for plasma protein C. In this assay protein C is adsorbed to Al(OH)3, eluted and activated by thrombin, after which the concentration of the activated protein C is measured with a peptide substrate (S2366). Normal values for protein C activity and protein C antigen were determined in healthy volunteers and patients on stable oral anticoagulant treatment. Protein C activity and antigen levels were compared in 28 patients from 9 different pedigrees with both congenital protein C deficiency and thrombotic disease. Two types of protein C deficiency could be recognized: in type I the deficiency is due to the absence or reduced presence of protein C molecules, while in type II the deficiency is caused by the presence of an abnormal protein C molecule with strongly reduced functional activity.
Keywords: Protein C deficiency; Protein C activity; Protein C variant; Thrombotic disease